Hulawadu Application Development: Modernizing the Health Training Management System at the UNG Health Training Center through Website Technology - Suleman, Ibrahim; Dewi Suryaningsi Hiola (PT Inovasi Pratama Internasional, 2025)
This study aims to develop and evaluate a web-based application that can modernize the health training management system at the Health Training Center of Gorontalo State University (UNG). The application, named Hulawadu, is designed to improve efficiency in training management by providing features such as participant registration, training scheduling, material management, and training evaluation. This study focused on the application's usability, which was tested through a survey involving 45 respondents, consisting of instructors and training participants. The results showed that the Hulawadu application obtained excellent usability scores, with an average score between 4.3 and 4.6 on various aspects such as ease of use, interface responsiveness, user satisfaction, and effectiveness in training management. Most respondents were satisfied with the application, but several challenges related to the adaptation of users who are less familiar with digital technology were found. The results of this study provide evidence that web-based applications can modernize health training management efficiently and effectively.